Correlation between gold ore deposits and intrusive magmatism in South Tien Shan metallogenic province - B. Ya. Vikhter (Известия высших учебных заведений: Геология и разведка, 2017)
Basing on the structural-formational complexes study of the one of the largest in the world South Tien Schan gold ore province, the new conclusions of the spatial-temporal interrelation of the ore mineralization types, presented in it, have been done. The author’s perennial field works data and results of the cameral processing of the rock and thin sections collected by him have been used. Due to the intensive processing of the main deposits, described in the paper, a state of the excavations has been altered a lot, the observations, made earlier, have more significant meaning and deserve the acquaintance of the specialists.